CONSTIPATION PRECEDING PARKINSON'S DISEASE–META-ANALYSIS. Issue 11 (14th October 2015) - Adams-Carr, Kerala; Schrag, Anette; Shribman, Samuel; Bestwick, Jonathan; Lees, Andrew; Noyce, Alastair
Abstract : Constipation is a well-recognised non-motor feature of Parkinson's disease (PD) and has been reported to predate PD in a number of observational studies, in some cases by over two decades. A systematic review and meta-analysis was carried out following MOOSE criteria. The literature search was undertaken on 7 December 2014 using PubMed and the relevant search terms 'Parkinson's disease' and 'Constipation'. Articles were screened for suitability and included if they met the specific criteria: observational studies with a cohort or case–control design; cases were patients with PD according to standard clinical criteria; controls were healthy or had no history of neurological disease; cohorts were representative of the general population; constipation in controls was assessed over the same time period as for patients; original data were reported. Data were extracted and combined using a fixed-effects model. Nine studies were included in the meta-analysis. Constipation was associated with an OR of 2.28 (95% confidence interval 2.10-2.46; p<0.001) for subsequent PD, offering further evidence that people with constipation are at a higher risk of developing PD and constipation may predate PD diagnosis by many years. This could have implications for our understanding of the pathogenesis of disease and planning of neuroprotective interventional trials.